2019
DOI: 10.1002/mgg3.541
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral striatal necrosis due to homoplasmic mitochondrial 3697G>A mutation presents with incomplete penetrance and sex bias

Abstract: Background Heteroplasmic mitochondrial 3697G>A mutation has been associated with leber hereditary optic neuropathy (LHON), mitochondrial encephalopathy, lactic acidosis and stroke‐like episodes (MELAS), and LHON/MELAS overlap syndrome. However, homoplasmic m.3697G>A mutation was only found in a family with Leigh syndrome, and the phenotype and pathogenicity of this homoplasmic mutation still need to be investigated in new patients. Methods The clinical interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It can be familial or sporadic in origin. BSN pathology may also involve globus pallidus, tegmental nucleus, and substantia nigra brain regions under various diseased conditions ( 2 ). The most commonly associated pyramidal symptoms include spasticity, hyperreflexia, and weakness primarily related to upper motor neuron degeneration, leading to developmental regression or cognitive as well as motor deficits ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be familial or sporadic in origin. BSN pathology may also involve globus pallidus, tegmental nucleus, and substantia nigra brain regions under various diseased conditions ( 2 ). The most commonly associated pyramidal symptoms include spasticity, hyperreflexia, and weakness primarily related to upper motor neuron degeneration, leading to developmental regression or cognitive as well as motor deficits ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…All mtDNA variants had been associated with Leigh syndrome except the m.3700G>A variant reported in Leber hereditary optic neuropathy 19 . Other variants initially described in this neuropathy have later been recognized in families with Leigh syndrome, such as m.13513G>A, m.3697G>A, and 4171C>A20 20,21 …”
Section: Resultsmentioning
confidence: 99%
“…19 Other variants initially described in this neuropathy have later been recognized in families with Leigh syndrome, such as m.13513G>A, m.3697G>A, and 4171C>A20. 20,21 Most children with BBG T2-hyperintensity had Leigh syndrome, half of them caused by oxidative phosphorylation system structural subunits or assembly factor defects. 3,18 Other mitochondrial defects involved pyruvate dehydrogenase E1-α (PDHA1), mtDNA maintenance (SUCLG1), mitochondrial thiamine pyrophosphate carrier (SCL25A19), valine metabolism (ECHS1 and HIBCH), and mitochondrial lipoic acid synthesis (MECR).…”
Section: Discussionmentioning
confidence: 99%
“…The last group of through direct sequencing of PCR fragments of a 14-year-old index male hypertrophic cardiomyopathy (hCMP) patient, it was found that m.14757T> a, m.15236A>G, m.15314G> a resulted in amino acid residues in the Cyt b gene replace, Cyt b is very likely to be related to cardiomyopathy (Zarrouk-Mahjoub et al, 2015). The 3697G>A mutation can cause to isolated severe complex I defects, leading to lactic acidosis, central nervous system dysfunction and other metabolic syndromes (Zhong et al, 2019). Modification of proteins encoded by mtDNA is still a technical bottleneck at present.…”
Section: Mitochondrial Syndrome Mutant Mitochondrial Genesmentioning
confidence: 99%